Higher Education: Handbook of Theory and Research Volume 25 - Smart, John C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Published annually since 1985, the Handbook series provides a compendium of thorough and integrative literature reviews on a diverse array of topics of interest to the higher education scholarly and policy communities. Each chapter provides a comprehensive review of research findings on a selected topic, critiques the research literature in terms of its conceptual and methodological rigor, and sets forth an agenda for future research intended to advance knowledge on the chosen topic. The Handbook focuses on twelve general areas that encompass the salient dimensions of scholarly and policy inquiries undertaken in the international higher education community. The series is fortunate to have attracted annual contributions from distinguished scholars throughout the world.
The Role of Information in the Policy Process: Implications for the Examination of Research Utilization in Higher Education Policy -- From Theory to Action: Exploring the Institutional Conditions for Student Retention -- Reform Efforts in STEM Doctoral Education: Strengthening Preparation for Scholarly Careers -- Toward a More Complete Understanding of the Role of Financial Aid in Promoting College Enrollment: The Importance of Context -- The Pursuit of Student Success: The Directions and Challenges Facing Community Colleges -- Studying the Impact of Parental Involvement on College Student Development: A Review and Agenda for Research -- Achievement Emotions in Higher Education -- The Use of Panel Data Models in Higher Education Policy Studies -- Enlarging Our Understanding of Glass Ceiling Effects with Social Closure Theory in Higher Education -- Cultural Perspectives of Academia: Toward a Model of Cultural Complexity -- Research Libraries in the Twenty-First Century -- An Examination of Faculty Work: Conceptual and Theoretical Frameworks in the Literature -- Herding Cats and Big Dogs: Tensions in the Faculty-Administrator Relationship.
Keywords: Education; Curriculum planning; Education, Higher; Education; Higher Education; Curriculum Studies; Administration, Organization and Leadership; Educational Policy and Politics